Multifocal multisystem Langerhans cell histiocytosis - Anupam Das; Kenit Ardeshna; Jimish Bagadia (Wolters Kluwer Medknow Publications, 2017)
We hereby report a case of a male child who presented with multiple brown to red papules and plaques in a seborrheic distribution. Histology and immunohistochemistry findings were consistent with a diagnosis of Langerhans cell histiocytosis with multifocal and multisystem involvement (Letterer-Siwe type). The case is being reported for its rarity.